Analisis Problematika Program Food Estate di Era Menteri Pertahanan Prabowo Subianto dalam Perspektif Ekofeminisme - Awang Ginaris Putra Abrilian (INDO PUBLISHING, 2025)
This article discusses ecofeminist critique of the problems that occur in the food estate program under the leadership of Defense Minister Prabowo Subianto, with a focus on how patriarchal and capitalist systems are related to exploiting nature and women. Referring to sources from feminist writers such as Vandana Shiva, Maria Mies, and Zillah Eisenstein, this article argues that the food estate program, which has the potential to cause displacement of indigenous peoples, neglect of local community voices, and threaten local food culture, is closely related to the oppression of women. Through a qualitative approach and critical and textual analysis, this article shows how women as agents of change in environmental issues are often discredited and even impacted by the food estate program. By connecting the narratives of environmental destruction and women's oppression, this study provides alternative solutions for food estate programs, including: local community involvement, regenerative agriculture, and agroecology.